Flourishing as a Measure of Global Well-being in First Year Residents: A Pilot Longitudinal Cohort Study. (May 2021) - Lebares, Carter C; Greenberg, Anya L; Shui, Amy; Boscardin, Christy; van der Schaaf, Marieke
Background: Physician well-being is critical to optimal learning and performance, yet we remain without validated measures to gauge the efficacy of well-being curricula for trainees. This study evaluates initial evidence of flourishing as a valid measure of global well-being in postgraduate-year-1 residents (PGY-1s), providing a means of assessing well-being intervention efficacy. Study design: In this single-site study of PGY-1s participating in Enhanced Stress Resilience Training (ESRT), an online questionnaire of published measures was administered at baseline (T1, just before PGY-1), post-ESRT (T2, 7 weeks later), and at PGY-1 end (T3, 11 months later). The Mental Health Continuum (MHC) was used to assess our primary outcome variable, flourishing, a well-established metric of psychosocial thriving in non-physicians that can be treated continuously or categorically. Correlation between flourishing and both resilience (mindfulness and workplace support) and risk (emotional exhaustion, depersonalization, stress, depressive symptoms, anxiety, and workplace demand) factors was assessed at each time-point and longitudinally. Results: Forty-five interns completed the survey at T1, 37 at T2, and 21 at T3; 21 responded at all time points. MHC score was significantly positively correlated with mindfulness (β = 1.47, SE = 0.35, P  < .001) and workplace support (β = 2.02, SE = 1.01, P  = .05) longitudinally, and at all time points. Flourishing was significantly negatively correlated with depressive symptoms (β = −7.48, SE = 1.68, P  < .001), stress (β = −1.28, SE = 0.29, P  < .001), and anxiety (β = −1.74, SE = 0.38, P  < .001) longitudinally and at all time points, and significantly negatively correlated with emotional exhaustion (β = −2.65, SE = 0.89, P  = .003) longitudinally and at T1 (β = −3.36, SE = 1.06, P  = .003). Conclusion: Flourishing showed appropriate correlation with established resilience and risk factors, thus supporting its concurrent validity as a measure of global well-being in this population. As such, the MHC may provide a simple, meaningful assay of well-being and an effective tool for evaluating the efficacy of well-being interventions. Further validation requires a larger, multi-center study.